Iron supplementation enhances RSL3-induced ferroptosis to treat naïve and prevent castration-resistant prostate cancer - Federica Maccarinelli; Daniela Coltrini; Silvia Mussi; Mattia Bugatti; Marta Turati; Paola Chiodelli; Arianna Giacomini; Floriana De Cillis; Nadia Cattane; Annamaria Cattaneo; Alessia Ligresti; Michela Asperti; et al. (Cell Death Discovery, 2023)
Abstract Prostate cancer (PCa) is a leading cause of death in the male population commonly treated with androgen deprivation therapy that often relapses as androgen-independent and aggressive castration-resistant prostate cancer (CRPC). Ferroptosis is a recently described form of cell death that requires abundant cytosolic labile iron to promote membrane lipid peroxidation and which can be induced by agents that inhibit the glutathione peroxidase-4 activity such as RSL3. Exploiting in vitro and in vivo human and murine PCa models and the multistage transgenic TRAMP model of PCa we show that RSL3 induces ferroptosis in PCa cells and demonstrate for the first time that iron supplementation significantly increases the effect of RSL3 triggering lipid peroxidation, enhanced intracellular stress and leading to cancer cell death. Moreover, the combination with the second generation anti-androgen drug enzalutamide potentiates the effect of the RSL3 + iron combination leading to superior inhibition of PCa and preventing the onset of CRPC in the TRAMP mouse model. These data open new perspectives in the use of pro-ferroptotic approaches alone or in combination with enzalutamide for the treatment of PCa.